Community-based tourism initiatives in São Paulo conservation units: mapping of initiatives, benefits and challenges - Koga, Erika Sayuri Koga; Uyeti, Joyce Hiromi (Brazilian Journal of Production Engineering, 2022)
The research encourages discussions about the benefits, advances and challenges of Community-Based Tourism (CBT) within or around Protected Areas (PA) at São Paulo state. The main purpose is understanding the evolution of CBT in Brazil and in the world, to map the initiatives and establish the relationships between the main agents: communities, government and visitors. According to the methodology used, using primary and secondary data, it was possible to elucidate the mapping of 25 communities that carry out CBT activities in and around 30 PAs in São Paulo. According to interviews with leaders from five communities and a public manager of a PA, it was found that populations that are more internally organized or well-connected with CBT networks and the government are more strengthened and obtain results of benefits and advances, while in cases of major internal breakdowns or weak relationships, they present major challenges for the development of CBT.